Impact of Hyponatraemia at Clinical Stable-State on Survival in Patients with Chronic Obstructive Pulmonary Disease - Kwok WC; Yap DYH; Tam TCC; Lam DCL; Ip MSM; Ho JCM (International Journal of COPD)
Wang Chun Kwok,1 Desmond Yat Hin Yap,2 Terence Chi Chun Tam,1 David Chi Leung Lam,1 Mary Sau-Man Ip,1 James Chung Man Ho1 1Division of Respiratory and Critical Care Medicine, Department of Medicine, Queen Mary Hospital, The University of Hong Kong, Pokfulam, Hong Kong SAR, People’s Republic of China; 2Division of Nephrology, Department of Medicine, Queen Mary Hospital, The University of Hong Kong, Pokfulam, Hong Kong SAR, People’s Republic of ChinaCorrespondence: James Chung Man Ho, Clinical Associate Professor, Department of Medicine, School of Clinical medicine, LKS Faculty of Medicine, The University of Hong Kong, 4/F, Professorial Block, Department of Medicine, Queen Mary Hospital, 102 Pokfulam Road, Pokfulam, Hong Kong SAR, People’s Republic of China, Tel +852 22554999, Fax +852 28725828, Email jhocm@hku.hkIntroduction: Hyponatraemia has been suggested to be associated with morbidity and mortality among various medical disorders. Evidence on the association between stable-state hyponatraemia and prognosis in patients with chronic obstructive pulmonary disease (COPD) is lacking.Methods: All COPD patients followed up in a regional hospital in year 2015 were included, with their clinical outcomes reviewed in the subsequent eight years. Association between stable-state hyponatraemia and mortality was evaluated. Stable-state hyponatraemia is defined as baseline serum sodium levels, at least 90 days away from the last AECOPD < 135 mmol/L.Results: There were 271 COPD patients included. Hyponatraemia was associated with shorter overall survival with adjusted hazard ratio (aHR) 1.74 (95% CI = 1.07– 2.65, p = 0.026). The median overall survival was 3.05 years (95% CI = 2.65– 3.46) for patients in the hyponatraemia group, in contrast to 3.35 years (95% CI = 2.86– 3.83) for those without hyponatraemia. The highest baseline serum sodium levels were significantly negatively associated with annual acute exacerbation of COPD (AECOPD) and annual hospitalized AECOPD frequency in the follow-up period, with Pearson correlation coefficient of − 0.16 (p = 0.011) and – 0.14 (p = 0.027), respectively.Conclusion: Stable-state hyponatraemia was associated with increased mortality and probably AECOPD frequency among patients with COPD.Keywords: chronic obstructive pulmonary disease, acute exacerbation of chronic obstructive pulmonary disease, hyponatraemia, sodium, electrolyte